Study On The Law Of Ground Strata Subsidence And Movement Induced By Caving Mining Of Slowly Inclined Large And Thick Ore Body - Teng Li (E3S Web of Conferences, 2018)
Taking the Western District of Chengchao Iron Mine as engineering background, based on the GPS monitoring data of nearly 8 years and the record of the ground surface movement, the law of ground strata subsidence and movement is studied. The studies have shown that the surface movement caused by underground mining has the characteristics of time delay and displacement angle development has the law of jumping. The strata movement caused by mining is divided into the stage of overlying strata collapse and the collapse stage of surrounding rock to goaf. In the first stage, the vertical stress plays a leading role and rock failure is shown as a regular barrel collapse. In the second stage, horizontal tectonic stress plays a leading role and the collapse mechanism of rock strata can be explained by the cantilever beam theory. According to the mechanism of strata movement analysis, strata movement of Chengchao Iron is divided into six regions, which respectively included vertical subsidence area, toppling sliding zone, dumping area, deformation zone, cumulative deformation area and undisturbed zone. The results of this paper can provide a theoretical basis for the surface movement prediction of caving mining in similar metal mine.